Analisis Kinerja Keuangan pada Pemerintah Daerah Kota Jambi Tahun Anggaran 2019-2021 - Rizkiza Aurin; Iskandar Sam; Rahayu Rahayu (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
Analysis of Financial Performance in Jambi City Local Government Fiscal Year 2019 - 2021 is the title of this study. The purpose of this research is to assess the financial performance of the Jambi City Regional Government utilizing the Decentralization Ratio, Regional Financial Independence Ratio, Regional Financial Dependency Ratio, PAD Effectiveness Ratio, and Ratio Shopping Efficiency. This is a quantitative descriptive study. This study makes use of secondary data in the form of the Jambi City Government's Regional Budget Realization Report (APBD) for the 2019 - 2021 Fiscal Year. The results demonstrate that the Jambi City Government's Financial Performance, as measured by the Ratio of Degrees of Decentralization, is classified as incapable of carrying out decentralization efficiently. The proportion Regional Financial Independence is defined as still relying on central and/or provincial government support, which is very high, and has not demonstrated independence in its regional financial performance. The Regional Financial Dependence Ratio classifies regions as having a strong reliance on the federal and/or provincial governments. It is effective since it is in the range of 90% - 99%, and the Expenditure Efficiency Ratio is efficient.